Architecture as Image of Landscape (diségno, 2024)
The concept of paesaggio/landscape was born and develops within representation, within the mimetic practices of artists, the same practices that closely concern architecture itself, not only in its ideational and constructive process but also in its semantic mission. Thus architecture participates in the construction of the landscape in many ways at the same time: it contributes through buildings that ignore it or with buildings that instead imitate the image, the form or the processes that form the landscape itself. But designing the landscape means operating both on the tangible level of the territory and on the intangible level of the ideas that orient its perception. In this sense, architecture also participates through buildings capable of influencing individuals and changing their way of observing the environmental components. A general reflection on representation introduces first the birth and then the contemporary evolution of the landscape in order to frame the theoretical contribution implicit in some modern and contemporary designers who have adopted the landscape as a medium to re-establish architecture itself –from Le Corbusier to Rem Koolhaas or Enric Miralles– or to provide it with at least an apparent compatibility in terms of environmental sustainability.
Keywords: Le Corbusier; Rem Koolhaas; representation; architecture as landscape; imitation